Energy Expenditure and Physical Activity in Recovering Malnourished Infants - Russell Rising; Gul Tiryaki Sonmez (Journal of Nutrition and Metabolism)
Background. Malnourished infants are small for age and weight. Objectives. Determine profiles in 24-hour energy metabolism in recovering malnourished infants and compare to similarly aged healthy controls. Methods. 10 malnourished infants (58.1±5.9 cm, 7.7±5.6 months) were healthy prior to spending 22 hours in the Enhanced Metabolic Testing Activity Chamber for measurement of EE (kcal/min), sleeping metabolic rate (SMR; kcal/min), respiratory quotient (RQ; VCO2/VO2), and physical activity (PA; oscillations in wt/min/kg body weight). Metabolic data were extrapolated to 24 hours (kcal/kg/d). Energy intake (kcal/kg/d) and the proportions (%) of carbohydrate, protein, and fat were calculated. Anthropometrics for malnourished infants were obtained. Statistical differences (P<.05) between groups were determined (SPSS, version 13). Results. In comparison to controls, malnourished infants were lighter (4.1±1.2 versus 7.3±0.8 kg; P<.05), had less body fat % (10.3±7.6 versus 25.7±2.5), and lower BMI (12.0±1.7 versus 15.5±1.5; P<.05). In contrast, they had greater energy intake (142.7±14.6 versus 85.1±25.8; P<.05) with a greater percentage of carbohydrates (55.1±3.9 versus 47.2±5.2; P<.05). However, malnourished infants had greater 24-hour EE (101.3±20.1 versus 78.6±8.4; P<.05), SMR (92.6±17.1 versus 65.0±3.9; P<.05), and RQ (1.00±0.13 versus 0.86±0.08; P<.05) along with a lower amount of PA (2.3±0.94 versus 4.0±1.5; P<.05). Conclusions. Malnourished infants require more energy, possibly for growth.